Cervical Spondylosis among Group of Computer Users in Erbil City - Al-Bustany, Dashty Abbas; Aziz, Zekra Ali (Zanco Journal of Medical Sciences (ZJMS), 2009)
Background and objective: Neck pain due to poor posture, if neglected for long time, can lead to development of the cervical spondylosis. This study was designed to analyze the relation between symptoms and signs originating from the cervical spine and the duration of computer use. Methods: A comparison of a group of male subjects who work on computer with those who do not work on computer whose ages range between (30 - 50) years was done for liability of cervical spondylosis. Any subject whose BMI is more than 25Kg/m2 was excluded. Likewise any subject with recognized evidence for predisposition to develop spondylosis was excluded.Employee from different establishments in Erbil City (200 Subjects), over a period of six months from January / 2008 were included in the study.Ninety nine subjects who use computer and hundred and one non-computer user. Subjects were subdivided into: First group: Computer user. Second group: Non-computer user. In both groups the duration of occupation ranges between four to sixteen year and hours of working/week range between (22-32 hours). The (99) subjects who work on computer each of them was evaluated for computer work station and asked about his posture during use of computer and asked if he takes a break time when he work for long hours.The difference between comparable subdivisions of the studied subjects was tested by the Chi-square test concerning the frequency of spondylosis in each of them. Results: Cervical spondylosis was statistically significant among those who use computer (P< 0.05). Conclusion: Long term use of computer with bad posture and with out break time increase liability for developing cervical spondylosis in comparison of (same age group, same duration of occupation ,and same hours of working) but not using computer. Proper posture and take a break time when using computer for long time is necessary.